Lectins (hemagglutinins) in the gut of the important disease vectors - Grubhoffer, L; Hypsa, V; Volf, P (Parasite (Paris, France), 1997)
The review is devoted to the gut lectins/hemagglutinins of the following representatives of important disease vectors: ticks, kissing-bugs, mosquitoes, sandflies and tsetse flies. The paper surveys the recent knowledge on these carbohydrate binding factors with respect to their structural and functional properties, and their significance for pathogen/parasite transmission by the blood-sucking arthropods. Recent results suggest that in most vectors the gut lectin activities are blood-meal enhanced, might participate in blood-meal processing and digestion and could serve as antibacterial and antiparasitic agents.
Keywords: lektiny; Animals; Disease Vectors; Lectins; Intestines; infekce přenášené vektorem; střeva; zvířata; hmyz - vektory; Arthropod Vectors; členovci - vektory; Insect Vectors